2014
DOI: 10.3354/meps10870
|View full text |Cite
|
Sign up to set email alerts
|

Dominant macrobenthic populations experience sustained impacts from annual disposal of fine sediments on sandy beaches

Abstract: Disposal onto a sandy beach of sediments dredged from a navigation channel suppresses abundances of most intertidal invertebrates and increases surf-zone turbidity (insets).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…These results regarding Emerita analoga and polychaetes conflict with the findings of previous studies, which reported pronounced negative effects of replenishment on Emerita talpoida (Hayden & Dolan, 1974;Peterson et al, 2000aPeterson et al, , 2006Peterson et al, , 2014Leewis et al, 2012;Manning et al, 2014) and positive or neutral effects on Scolelepis sp. and/or polychaetes in general (Menn et al, 2003;Peterson et al, 2006Peterson et al, , 2014Leewis et al, 2012;Manning et al, 2014; but see Schlacher and Thompson, 2012). The response of E. analoga may be explained in part by processes other than replenishment that produce boom-bust cycles.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results regarding Emerita analoga and polychaetes conflict with the findings of previous studies, which reported pronounced negative effects of replenishment on Emerita talpoida (Hayden & Dolan, 1974;Peterson et al, 2000aPeterson et al, , 2006Peterson et al, , 2014Leewis et al, 2012;Manning et al, 2014) and positive or neutral effects on Scolelepis sp. and/or polychaetes in general (Menn et al, 2003;Peterson et al, 2006Peterson et al, , 2014Leewis et al, 2012;Manning et al, 2014; but see Schlacher and Thompson, 2012). The response of E. analoga may be explained in part by processes other than replenishment that produce boom-bust cycles.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies of the effects of replenishment on polychaetes (Menn et al, 2003;Leewis et al, 2012;Manning et al, 2014;Peterson et al, 2006Peterson et al, , 2014 often focused on a single species, Scolelepis squamata. None reported long-term negative effects and in some cases replenishment had a positive effect on the polychaete(s) studied (Menn et al, 2003;Leewis et al, 2012;Manning et al, 2014). In our study, Thoracophelia sp., Nephtys californiensis, Hemipodia simplex, Naineris dendritica, Orbinia johnsoni, and unknown polychaetes accounted for a large proportion (24%) of all collected invertebrates, were found in approximately equal numbers, and in aggregate were twice as abundant as Scolelepis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, juvenile, recently molted, and gravid female crabs may have increased susceptibility to the effects of burial and forces associated with the lateral surge. Crab size and reproductive state should be considered to ameliorate negative effects of deposition events on sensitive stages [3]. Based on size-frequency measurements from crab pot deployments, most crabs observed at BVLs were adults 100 – 170 mm carapace width, and densities of smaller juvenile crabs were generally lower in nearshore samples compared to estuary habitat during the period of deposition operations [39, 40] However, new recruits < 30 mm were observed during 2016 in both video and crab pot samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in dredged sediment management include recognition of the potential to mitigate areas of environmental degradation with judicious sediment placement [13]. Such “beneficial uses” include creation, restoration, and maintenance of wetland habitat, and nourishment of eroding ocean beaches.…”
Section: Introductionmentioning
confidence: 99%
“…Grain size dictates the makeup of benthic communities (e.g., [3][4][5][6]); even temporally varying fine-scale sedimentological variations such as sedimentological differences between peaks and troughs of mega ripples can force differences in community structure [7]. Therefore, anthropogenically forced variations in grain size can affect community structure [8,9]. From a morphodynamic perspective, grain size and cohesive properties not only dictate thresholds of erosion and deposition [10,11]-beach profile is related to grain size, as well e.g., [12,13].…”
Section: Introductionmentioning
confidence: 99%